SPATIAL MULTI-CRITERIA DECISION ANALYSIS FOR INDUSTRIAL SITE SELECTION: THE STATE OF THE ART - rikalovic, Aleksandar m; Cocić, Ilija (Journal of Applied Engineering Science, 2014)
Site selection is one of the basic vital decisions in the start-up process, expansion or relocation of businesses of all kinds. Starting  from the meeting criteria defined in the business strategy , location selection process begins as recognition of existing or projected need to meet new or growing market. Recognition of the need to initiate a series of activities directed for looking geographical area and specific location. Conquer new territories for business starts collecting geopolitical data, where location is a part of it. The selection of an industrial site involves a complex array of critical factors involving economic, social, technical, environmental,political issues, etc. It is obvious that many factors must be involved in the decision-making process, which makes the problem challenging choice in the selection of appropriate tools to enable concentration data, information and knowledge. New trends in information technologies put Geo-information technology in the center of events in industrial locations science. Like any technology that is trendy Geographic Information Systems have exaggerated the benefits and latent defects, but in choosing the industrial location allowing multi-criteria decision making based on space and time, in this time of technology are indispensable. Geographic Information Systems are used in conjunction with other systems and methods such as expert systems (ES), systems for decision making (DSS) and the method for multi-criteria decision making (MCDM). This paper presents the state of the art in Spatial multi-criteria decision analysis for industrial site selection.
Keywords: Spatial Decision Support Systems (SDSS); Multi-Criteria Decision Analysis (MCDA); Industrial Site Selection; Geographic Information Systems (GIS)